2005
DOI: 10.1142/s0192415x05002631
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of CML-1: An Herbal Formulation

Abstract: CML-1 is a purified extract from a mixture of 13 Oriental herbs (Achyranthis Radix, Angelicae Gigantis Radix, Cinnamomi Cortex Spissus, Eucommiae Cortex, Glycyrrhizae Radix, Hoelen, Lycii Fructus, Paeoniae Radix, Rehmanniae Radix Preparata and Atractylodis Rhizoma, Zingiberis Rhizoma, Zizyphi Semen, Acori Graminei Rhizoma) that have been widely used for the treatment of inflammatory diseases in Asia. The aim of this study was to investigate the anti-inflammatory and analgesic potential of CML-1. The animals us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Recently, our in vivo study has demonstrated that CML-1 has the anti-inflammatory effects (Eum et al, 2005). Although plantderived agents could be used alone, combined extracts may allow a reduction in side effects and possibly leading to an increase in effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our in vivo study has demonstrated that CML-1 has the anti-inflammatory effects (Eum et al, 2005). Although plantderived agents could be used alone, combined extracts may allow a reduction in side effects and possibly leading to an increase in effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study has shown that CML-1 has the anti-inflammatory and anti-nociceptive activities in various experimental in vivo animal models (Eum et al, 2005). However, the precise mech- anisms of action involved in the anti-inflammatory activities induced by CML-1 are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The YULDA-HANSO-TANG [Cool the Diaphragm and Dispel Fire Decoction] is applied to treat cerebral infection (Jeong et al, 2007); Prescriptions that contain Cinnamomi Ramulus or Ephedrae Herba that were used to treat contagious diseases or influenza in the ancient times are applied to atopic diseases and arthritis (Jeong et al, 2008;Sato et al, 1989;Chang et al, 1993;Kubo et al, 1996;Eum et al, 2005). Moreover, the fact that Oriental Medicine is being used in fields that did not get much attention in the ancient times, such as skin care and obesity treatment, tells us that Oriental Medicine does not depend on a certain ingredient in a drug that has a unique therapeutic effect toward a certain disease.…”
Section: Introductionmentioning
confidence: 99%
“…31 Hoelen, Citri Unshiu Pericarpium, Agastachis Herba, Spatholobi Caulis, Rhynchosia Nulubilis and Glycyrrhizae Radix have anti-inflammatory activity as immune modulators. [35][36][37][38][39][40] Hoelen blocks selective serotonin reuptake inhibitors (SSRIs), which can induce anorexia with serotonin, and Pinelliae inhibits the vomiting center in animal models. 43,44 Appetite, body weight, and survival are endpoints for anorexia management in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The current herbal decoction, which includes Astragali Radix, [31][32][33][34] Atractylodis Rhizoma Alba, Hoelen, [35][36][37][38] Pinelliae Tuber, Citri Unshiu Pericarpium, 39 Agastachis Herba, 40 Alismatis Rhizoma, Plantaginis Semen, 41 Spatholobi Caulis, 42 Zizyphi Fructus, Rhynchosia Nulubilis, Crataegi Fructus, Galli Stomachichum Corium, and Glycyrrhizae Radix, is an immune modulator, is renoprotective, reduces lactate dehydrogenase, and increases gastrointestinal function. [43][44][45][46] This mixture has been developed to improve gastrointestinal function and modulate the immune system to treat anorexia.…”
Section: Introductionmentioning
confidence: 99%